2016
DOI: 10.1177/0019793916640492
|View full text |Cite
|
Sign up to set email alerts
|

Who Cares about the Health of Health Care Professionals? An 18-Year Longitudinal Study of Working Time, Health, and Occupational Turnover

Abstract: Health care workers are employed in a complex, stressful, and sometimes hazardous work environment. Studies of the health of health care workers tend to focus on estimating the effects of short-term health outcomes on employee attitudes and performance, which are easier to observe than long-term health outcomes. Research has paid only scant attention to work characteristics that are controlled by the employer and its employees, and their relationship to employees’ long-term physical health and organizational o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 59 publications
1
12
0
1
Order By: Relevance
“…The identified COVID-19 related stressors that are experienced by nurses, so far, are multifactorial. Among others, pandemic-related worries and concerns, as well as a lack of pandemic-related information, could be identified as some of the main triggers for pandemic-related stress among nurses [ 3 , 4 , 5 ]. Likewise, the mental health outcomes of the pandemic-related stress experience of nurses in national and international contexts are already evident.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identified COVID-19 related stressors that are experienced by nurses, so far, are multifactorial. Among others, pandemic-related worries and concerns, as well as a lack of pandemic-related information, could be identified as some of the main triggers for pandemic-related stress among nurses [ 3 , 4 , 5 ]. Likewise, the mental health outcomes of the pandemic-related stress experience of nurses in national and international contexts are already evident.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, there was no difference in pandemic-related worries and concerns between frontline and non-frontline healthcare professionals [ 36 ]. However, other studies provide evidence that stress levels are higher among healthcare professionals who have direct contact with COVID-19 positive patients than those without contact with infected patients [ 4 , 13 , 37 ]. Similar findings were also identified among nurses during the SARS outbreak, with those with direct contact with SARS-infected patients experiencing more severe psychological consequences such as anxiety, depression, burnout, somatization, post-traumatic stress disorder, than those without direct contact with infected patients.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the increasing need for professional outpatient caregivers, there are shortages of skilled workers and early retirements [4] as well as more days of incapacity for work in care occupations compared to other employee groups in Germany [5]. Several studies on healthcare workers and nurses reported a high prevalence for overweight, obesity and metabolic syndrome [6][7][8] and an association of obesity with longer working hours [9]. Obesity and metabolic syndrome increase the risk of cardiovascular disease and type 2 diabetes mellitus [6,[10][11][12] and an inadequate diet and physical inactivity have been reported as the most common antecedents for metabolic syndrome and cardiovascular disease [11].…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…It is also observed that both the industrial context and national boundary conditions are important for contextualizing OHS research. For instance, some scholars (Kramer & Son, 2016;Poplin et al, 2008;Zytoon, 2012) were interested in investigating accident types and causes in featured industries, such as health care and mining, while others tended to explore OHS within national boundary conditions, such as distributions of OHS risks between immigrants and non-immigrants in countries with favorable migration policies (Smith & Mustard, 2010;Sønderstrup-Andersen & Bach, 2018). The regulatory and legislative aspects of OHS were also salient in the content analysis.…”
Section: Theme Two: Industrial Policy and Regulations Around Ohsmentioning
confidence: 99%